2019
DOI: 10.1111/dom.13744
|View full text |Cite
|
Sign up to set email alerts
|

Role of apolipoprotein C‐III overproduction in diabetic dyslipidaemia

Abstract: Aims: To investigate how apolipoprotein C-III (apoC-III) metabolism is altered in subjects with type 2 diabetes, whether the perturbed plasma triglyceride concentrations in this condition are determined primarily by the secretion rate or the removal rate of apoC-III, and whether improvement of glycaemic control using the glucagon-like peptide-1 analogue liraglutide for 16 weeks modifies apoC-III dynamics.Materials and Methods: Postprandial apoC-III kinetics were assessed after a bolus injection of [5,5,5-2 H 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 64 publications
2
43
0
Order By: Relevance
“…It has been proposed that glucose-mediated regulation of APOC3 expression promotes a shift in the energy source for peripheral tissues from fatty acids released by lipolysis of TRLs to increased utilization of blood glucose ( 28 , 31 , 41 , 42 ). APOC3 expression is therefore upregulated in states of insulin resistance (characterized by insulin resistance and hyperglycemia), and recent results demonstrate that glycaemic control is a major determinant of apoC-III secretion rate in vivo (as measured by stable isotope technology) and thus plasma apoC-III levels ( 43 ). In these studies it was reported also that apoC-III metabolism is significantly perturbed in subjects with type 2 diabetes; the apoC-III secretion rate was markedly higher than that seen in BMI-matched non-diabetic controls.…”
Section: Structure and Regulation Of Apoc-iiimentioning
confidence: 99%
See 2 more Smart Citations
“…It has been proposed that glucose-mediated regulation of APOC3 expression promotes a shift in the energy source for peripheral tissues from fatty acids released by lipolysis of TRLs to increased utilization of blood glucose ( 28 , 31 , 41 , 42 ). APOC3 expression is therefore upregulated in states of insulin resistance (characterized by insulin resistance and hyperglycemia), and recent results demonstrate that glycaemic control is a major determinant of apoC-III secretion rate in vivo (as measured by stable isotope technology) and thus plasma apoC-III levels ( 43 ). In these studies it was reported also that apoC-III metabolism is significantly perturbed in subjects with type 2 diabetes; the apoC-III secretion rate was markedly higher than that seen in BMI-matched non-diabetic controls.…”
Section: Structure and Regulation Of Apoc-iiimentioning
confidence: 99%
“…In these studies it was reported also that apoC-III metabolism is significantly perturbed in subjects with type 2 diabetes; the apoC-III secretion rate was markedly higher than that seen in BMI-matched non-diabetic controls. Improved glycaemic control with the glucagon-like peptide (GLP)−1 analog liraglutide for 16 weeks reduced the apoC-III secretion rate and as a consequence plasma apoC-III levels ( 43 ). These findings demonstrate that glucose homeostasis is an important regulator of apoC-III metabolism, and that the secretion rate of apoC-III is an important driver for the elevation of TRLs in subjects with type 2 diabetes ( 43 ).…”
Section: Structure and Regulation Of Apoc-iiimentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that our results show the association between the apolipoprotein C and T2DM. Since there are limited studies in this area [51,52], we will pay more attention to the changes in apolipoprotein C during the progress of T2DM in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The HTG is thought to be due to TGL overproduction in type 2 diabetes as a result of increased release of free fatty acids from adipose tissue, enhanced hepatic lipogenesis and increased secretion of large TRL particles by the liver as well as the intestine as a consequence of insulin resistance and hyperglycemia (39). Although LPL activity is known to be decreased in insulin deficient states (40), recent developments in the understanding of LPL regulation have also shown that insulin resistance leads to increased APOC3 and ANGPTL4, which reduce LPL activity and TGR remnant particle clearance (41)(42)(43).…”
Section: Diabetesmentioning
confidence: 99%